A STUDY ON INFLAMMATORY DISEASES OF THE EXTERNAL EAR - Jay Kothari; Nipa Dalal; Alpesh Patel; Kinnari Rathod; Vaishvi Hindia (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
Inflammatory diseases of the external ear are common in both otorhinolaryngology and primary care due to the ear's exposed anatomical location, making it susceptible to trauma, environmental factors, and infections. This study aimed to explore the etiological factors, clinical features, treatment methods, outcomes, and complications associated with external ear inflammations. A prospective observational study was conducted on 400 patients who underwent ENT examination and treatment at a Tertiary Care Center from 2020 to 2023. The male-to-female ratio was 1.2:1. The most common cause was bacterial infections, with otomycosis being the most prevalent condition. Earache was the most frequent symptom. Seventy-four percent of patients recovered with medical management alone, and the complication rate was 10%. Otomycosis, often influenced by hot and humid environments, primarily affected younger individuals due to increased exposure. Most diagnoses were clinical, and conservative treatment proved effective, reducing the need for further investigations.